HUBUNGAN INDEKS MASSA TUBUH (IMT) DAN TEKANAN DARAH DENGAN KEJADIAN ASAM URAT PADA LANSIA - Nella Hetty Sinaga; Savitri Gemini; Siska Pratiwi (Ensiklopedia of Journal, 2026)
Uric acid is the end result of catabolism (breakdown) of a substance called purine. Purine substances are natural substances which are one of the groups of chemical structures that form DNA and RNA.. This research is a quantitative study, using an analytic design with a cross sectional approach with the affordable population in this study were all elderly people in the Sei Langkai Health Center Working Area in 2024, totaling 203 elderly gout. The sampling method technique used in this researcher uses simple random sampling by measuring body mass index in the elderly, which consists of measuring body weight using a weight scale in kilograms and height in the elderly using a stature meter in centimeters and measuring blood pressure using a tensimeter, then measuring uric acid in the elderly using Easy Touch. P-value of 0.000, which means that there is a strong correlation between BMI and uric acid levels in the elderly and there is a significant relationship between blood pressure and the incidence of gout, with a P-value of 0.000.Keywords: Body Mass Index, Blood Pressure, Uric Acid, Elderly